(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Posyandu Remaja UPT Puskesmas Ibrahim Adjie is one of the realizations of the government program, where the implementation of activities takes place every Saturday and Sunday in the first week of each month. Technically, the implementation is integrated with various other activities such as posbindu, PPKS, youth organization meetings, or other youth activities. This activity has been running since 2018. The problem of partners raised in the Community Service Activity program is that the role of cadres in the implementation of adolescent posyandu is not optimal, as well as the many problems in adolescent reproductive health. The methods that have been carried out include; 1) conducting free health checks, giving Fe Tablets and reproductive health counseling, and 2) conducting training for adolescent posyandu cadres. The results of this service stated that a significance value (2tailled) of 0.000 <0.05 indicated a significant difference between the pre-test and post-test. This shows a significant increase in knowledge in adolescent posyandu cadres after training on Islamic holistic reproductive health. The conclusion of this activity is very successful and is expected to have an impact on increasing the effectiveness and participation of adolescents in youth posyandu activities